Application of Sanctions for State Civil Apparatus Who Violate Personnel Discipline Case Study in Office Offices Education and Culture of Medan City - Majidah Pohan; Yasmirah Mandasari Saragih; Tamaulina Br. Sembiring (Green Social: International Journal of Law and Civil Affairs, 2025)
In order to achieve national goals, a State Civil Apparatus is required, this is regulated in Article 12 of Law no. 20 of 2023 states that: "ASN employees play the role of planners, implementers and supervisors of the implementation of general government tasks and national development through the implementation of professional policies and public services, free from political intervention, and free from practices of corruption, collusion and nepotism. Every ASN must have high abilities and qualities and be balanced with high work discipline. The level of employee discipline is seen from attendance which is calculated from coming and going home, dressing neatly, carrying out duties and obligations on time, and. not committing acts that violate the provisions of the Law. This research uses a type of empirical juridical research, namely research that is directly carried out by researching in the field and directly visiting the location that is the research material with the focus being field research research, we seek answers to the efforts of the Medan City Regional Civil Service Agency in implementing sanctions for State Civil Service Employees who violate the rules regarding work discipline. Research findings show that there are still state civil servants in the Medan City Education Office who commit disciplinary violations, including minor, moderate and serious violations. In its implementation, enforcement of sanctions against State Civil Apparatus in the Government Area of ​​the Medan City Education Service is carried out according to established rules. These regulations are stated in Law Number 5 of 2014 concerning State Civil Apparatus and Regulation of the Mayor of Medan, North Sumatra Province No. 58 of 2023. The mechanism includes that if there is a violation, the ASN will be summoned. The summons is intended to carry out an inspection process by the Examination Team. After the examination is carried out and the mistake is proven, the ASN concerned is sentenced to punishment as regulated in Article 7 paragraph (1) of the government regulation, consisting of three levels of disciplinary punishment, including light disciplinary punishment consisting of an oral warning , a written warning and a statement of dissatisfaction. in writing. The type of moderate disciplinary punishment consists of postponing periodic salary increases for one year, postponing promotions for one year, and demotion to a lower level for one year. Meanwhile, the types of severe disciplinary punishment consist of demotion to a lower level for three years, transfer in order to be demoted to a lower level, release from office, honorable dismissal not at one's own request as an ASN, and dishonorable dismissal as a State Civil Apparatus.